The coronavirus pandemic as an analogy for future sustainability challenges - Engler, John-Oliver (Sustain Sci, 2020)
The current coronavirus outbreak may provide an illustrative analogy for sustainability challenges, exemplifying how challenges such as climate change may become wicked problems demanding novel and drastic solution attempts.